Pregled vrednotenj naravoslovnega znanja v prvem vzgojno-izobraževalnem obdobju osnovne šole - Kožuh, Vasja; Plazar, Janja (Revija za elementarno izobraževanje, 2021)
An overview of Science Knowledge Evaluation in the First Three Grades of Elementary School. This paper presents an overview of Slovenian elementary school evaluation of students’ natural science knowledge in the first three years of elementary school. Science knowledge in Slovenia is not measured regularly; therefore, we have focused primarily on the results of the international TIMSS survey, which measures the mathematical and natural science knowledge of students. The TIMMS survey is performed every four years in various countries, and Slovenia participated from 1995 to 2015. After reviewing and analysing the results of the natural science examinations of Slovenian fourth-graders, we found a steady increase compared to the international average. However, at the same time, the positive attitude towards science lags behind.
Keywords: knowledge evaluation; natural sciencesželementary school students; international TIMSS survey